PENGETAHUAN DAN PERILAKU PETANI TERHADAP PENGGUNAAN PESTISIDA KIMIA DALAM PENGENDALIAN ORGANISME PENGGANGGU TANAMAN JAGUNGDI KECAMATAN TANAMBULAVA - Fikriansyah, Moh.; Saleh, Shahabudin; Hasriyanty, Hasriyanty (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
Central Sulawesi Province is a significant corn-producing region in Indonesia, with an average production of 193,522.8 t/year from 2013-2017. Sigi Regency, one of the largest corn producers in the province, has a harvest area of 10,700 ha, yielding 44,115 t annually, with an average productivity of 4.2 t/ha. Despite the prevalence of chemical pest control methods among farmers, awareness of the negative impacts of these chemicals is limited. This study aims to analyze the knowledge and behavior of farmers regarding pesticide use for maize pest control in Tanambulava District. The research was conducted in five villages within the district in 2022. Data were collected through interviews using a questionnaire, involving 45 farmers from 15 farmer groups, selected through purposive sampling. The study found that the knowledge of maize farmers in Tanambulava Subdistrict about pesticide use was relatively low. Many farmers lacked information on the proper use of chemical pesticides and their adverse effects on the environment and non-target organisms, leading them to prefer chemical control methods. The behavior of farmers in using pesticides is often incorrect, with practices such as mixing multiple pesticide types in one application and using dosages that deviate from recommendations. Differences in farmers' knowledge and behavior appear to be associated with variations in education level, age, and farming experience.